2022
DOI: 10.1111/edt.12741
|View full text |Cite
|
Sign up to set email alerts
|

Quality and accuracy of patient‐oriented Web‐based information regarding tooth avulsion

Abstract: Background/Aim Tooth avulsion (TA) is a severe form of traumatic dental injury. The tooth's prognosis depends on the immediate measures taken. First responders are often laypeople, and the Internet is a favored platform to access health‐related information. The aim of this descriptive study was to evaluate the accuracy, quality, readability, and popularity of patient‐oriented web information regarding the emergency management of TA. Methods Three search engines (Google, Bing, and Yahoo.com) were browsed with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…According to the DISCERN score, Alpaydin et al found the highest rates in the very poor category at 43.3% and the poor category at 44.1% [23]. Considering similar studies, this rate was reported as 47.6% fair [12], approximately 50% fair [24], and poor information quality compared to the average score [25].…”
Section: Resultsmentioning
confidence: 95%
“…According to the DISCERN score, Alpaydin et al found the highest rates in the very poor category at 43.3% and the poor category at 44.1% [23]. Considering similar studies, this rate was reported as 47.6% fair [12], approximately 50% fair [24], and poor information quality compared to the average score [25].…”
Section: Resultsmentioning
confidence: 95%
“…An avulsed permanent tooth is a serious traumatic dental injury (TDI), which should be dealt with immediately 1,2 . The prognosis is very much dependent on decisions at the place of the accident and the time immediately after the avulsion has taken place 2 .…”
mentioning
confidence: 99%
“…An avulsed permanent tooth is a serious traumatic dental injury (TDI), which should be dealt with immediately 1,2 . The prognosis is very much dependent on decisions at the place of the accident and the time immediately after the avulsion has taken place 2 . The preferred treatment for an avulsed permanent tooth is replanting the avulsed tooth back into its socket, which should be carried out as soon as possible to have the best outcome 2,3 .…”
mentioning
confidence: 99%
See 1 more Smart Citation